Unicity of Entire Functions concerning Shifts and Difference Operators - Dan Liu; Degui Yang; Mingliang Fang (Abstract and Applied Analysis)
We prove a unicity theorem of entire functions that share two distinct small functions with their shifts. The corollary of the theorem confirms the conjecture posed by Li and Gao (2011).